THE RELATIONSHIP BETWEEN FORCE-EXTENSION DIAGRAM AND VISUAL INSPECTION ON THE EDGE CRACKING TENDENCY OF DUAL PHASE STEELS - Ardali, Refiye; Yildirim, Omer; Sahin, Kubilay; Saray, Onur (Tanger Ltd, 2018)
Light-weighting targets of the automotive sector requires to use of advanced high-strength steels (AHSS) with higher strength more extensively. However, as a common behavior, increasing strength levels of AHSS accompanied with decreasing ductility/formability levels. This behavior become more pronounced during secondary deformation of a blanked edge. To examine this concept, hole expanding (HE) test, that simulates the local formability of the edges after blanking operations, has been started to be widely used. In this study, deformation stages of the HE tests were examined by means of main characteristics and variations of F (force) - X (extension) curves and derivative of F with respect to the X (dF/dx) during the punch travel until cracking. In order to correlate variation in curve characteristics with deformation stages, high-resolution camera images of the tested samples concurrently collected during the whole test and main relationships between them were determined. Based on these relationships a new approach to predict "stop stroke" of the HE tests is proposed. Therefore, elimination of the visual inspection and decision making of an operator or an in-situ image processing software is aimed. Proposed approach was developed using DP600 steel with a thickness of 1.2 mm as a common steel grade that widely used in automotive industry. Also, validation of developed "stop stroke" criteria was tried in HE testing of thinner and thicker DP600 samples. Results showed that a good prediction of stop stroke can be achieved by using proposed approach.
27th International Conference on Metallurgy and Materials (METAL) -- MAY 23-25, 2018 -- Brno, CZECH REPUBLIC
Keywords: Hole expansion; local formability; dual phase steels; edge cracking